2004
DOI: 10.1016/j.bbamem.2004.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the membrane localization and distribution of flavonoids by high-resolution magic angle spinning NMR spectroscopy

Abstract: To investigate the structural basis for the antioxidative effects of plant flavonoids on the lipid molecules of cellular membranes, we have studied the location and distribution of five different flavonoid molecules (flavone, chrysin, luteolin, myricetin, and luteolin-7-glucoside) with varying polarity in monounsaturated model membranes. The investigated molecules differed in the number of hydroxyl groups attached to the polyphenolic benzo-gamma-pyrone compounds. To investigate the relation between hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
111
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(125 citation statements)
references
References 47 publications
9
111
0
5
Order By: Relevance
“…Intrinsic fluorescence properties of fisetin were used by Sengupta et al [7] to show that this molecule was localized and rigidly bound at the polar/apolar interfacial region of lipid bilayer. In a series of 1 H magic angel spinning NMR experiments it was shown that in fact flavonoid molecules are broadly distributed along the membrane normal with a maximal probability of localization close to polar/apolar interface [8]. After intercalation of flavonoids into membrane the antioxidant effects can be achieved by the two complementary mechanisms -i) direct scavenging of ROS by flavonoid molecules and/or ii) reduction of the ROS access to the interior of membrane caused by flavonoidinduced alteration of membrane fluidity.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic fluorescence properties of fisetin were used by Sengupta et al [7] to show that this molecule was localized and rigidly bound at the polar/apolar interfacial region of lipid bilayer. In a series of 1 H magic angel spinning NMR experiments it was shown that in fact flavonoid molecules are broadly distributed along the membrane normal with a maximal probability of localization close to polar/apolar interface [8]. After intercalation of flavonoids into membrane the antioxidant effects can be achieved by the two complementary mechanisms -i) direct scavenging of ROS by flavonoid molecules and/or ii) reduction of the ROS access to the interior of membrane caused by flavonoidinduced alteration of membrane fluidity.…”
Section: Introductionmentioning
confidence: 99%
“…A similar localization was reported for genistein in DMPC membranes [70]. Additionally, it was shown that the spatial orientation in the bilayer depended on the position of the polar centre of the flavonoid molecule [69]. According to the model of Scheidt et al [69], we postulate that the flavonols morin and myricetin were located with their B rings pointing towards the aqueous phase, while their A rings were inserted deeper into the acyl chain region of the membrane.…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, it was shown that the spatial orientation in the bilayer depended on the position of the polar centre of the flavonoid molecule [69]. According to the model of Scheidt et al [69], we postulate that the flavonols morin and myricetin were located with their B rings pointing towards the aqueous phase, while their A rings were inserted deeper into the acyl chain region of the membrane. On the other hand, apigenin and acacetin were more likely to be oriented with their B rings heading for membrane centre and A rings located closer the surface of the lipid bilayer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most flavonoids, mainly due to their lipophilicity, have the tendency to accumulate in biological membranes, particularly in lipid rafts, where they can interact with different receptors and signal transducers and influence their function through the modulation of the lipid-phase behavior [54]. In vitro studies demonstrated that compounds differing in the number of hydroxyl groups showed a broad distribution along the membrane [55].…”
Section: Discussionmentioning
confidence: 99%